Examination of the Causes and Consequences of International Migration in Nigeria - Duru, Innocent U (Asian Development Policy Review, 2021)
This study examined the leading causes and consequences of international migration in Nigeria. A survey research design was utilized for the study. The data was collected through a structured questionnaire. The opinions of 100 respondents selected through the purposive sampling technique were obtained on the principal causes and consequences of international migration in Nigeria. The findings revealed that the principal causes of international migration in Nigeria were job opportunities, unemployment, wealth prospects, safety and security, better conditions of service, low salaries and higher standards of living. These foremost causes of international migration in Nigeria were mostly economic factors. Furthermore, the findings showed that the foremost positive and negative effects of international migration in Nigeria were integrated development, increase in remittances, cheap and surplus labour, urban services and social infrastructure under stress, stricter immigration norms, multi-ethnic society and increased tolerance, Xenophobia, close gaps in skills and cultural dilution. These effects were economic, social and political. Among others, the study, thus, recommends that: the strategies of the government for stemming international migration should address push factors of unemployment, safety and security and low salaries and pull factors such as job opportunities, wealth prospects, better conditions of service and higher standards of living since they are the root causes of international migration. Furthermore, migration, a long-standing poverty reduction and strategy for human development need to be mainstreamed into policies of development in Nigeria at the Federal, State and Local Governments.